2016
DOI: 10.5858/arpa.2016-0403-oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics and Mutational Status of Succinate Dehydrogenase Genes in Paraganglioma of the Urinary Bladder: A Multi-Institutional Korean Study

Abstract: Context.-Because of the limited number of available primary bladder paraganglioma (PBPG) cases, the rates of succinate dehydrogenase (SDH) mutations and the clinicopathologic characteristics of SDH-deficient tumors have not been fully studied.Objective.-To define the clinicopathologic and molecular characteristics of PBPGs.Design.-A total of 52 PBPGs were collected retrospectively. SDHA and SDHB immunohistochemical stains were performed. In cases of SDHB expression loss, mutation analyses of SDHB, SDHC, and SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The risk of metastases is higher in patients with paraganglioma of the bladder and the mutation. Consequently, an intensified follow-up and surveillance should be considered when such SDHB mutations are found [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of metastases is higher in patients with paraganglioma of the bladder and the mutation. Consequently, an intensified follow-up and surveillance should be considered when such SDHB mutations are found [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, special attention should be paid when a SDBH mutation is found since the risk of metastases is higher in this group. The follow-up should be intensified [5,6]…”
Section: Discussionmentioning
confidence: 99%
“…PGL is associated with this syndrome caused by germline mutations in SDH [ 14 ]. Studies have demonstrated the association between PGLs in PHEO/PGLs syndrome and mutation in SDHB, SDHC, or SDHD genes [ 15 ]. PGLs in the thoracoabdominal region are associated with SDHB mutation whereas the head and neck PGLs are associated with SDHD.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in London on patients with bladder paraganglioma found pathogenic SDHB variants in 6/9 individuals, again mostly in male and younger individuals [ 25 ]. Although there have been several case series on urogenital paragangliomas in Asia, there is limited information on causative germline variants of these rare tumours [ 26 , 27 ]. In the few Asian genetic studies on urogenital paragangliomas, SDHB exon 7 deletion was reported in an Indian patient with bladder paraganglioma [ 28 ], while SDHB : c.112delC (p.Arg38fs) variant was reported in a Hong Kong Chinese patient with recurrent metastatic bladder paraganglioma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%